Optimizing Family Education Through Digital-Based Parenting Models: A Strategy for Improving Early Childhood Character in Jambi City - Ridwan Ridwan; Hayati Hayati; Anisah Anisah; Huda Huda; Ririn Anggraini (Journal of Childhood Development, 2026)
The increasing integration of digital technology into family life has transformed parenting practices and created new challenges in fostering early childhood character development. Despite the widespread use of digital media among young children, limited research has explored how parents in local communities understand and implement digital-based parenting in their daily lives. This study aimed to explore digital parenting practices and examine how parents utilize digital technology to support early childhood character development in RT 24, Pakuan Baru Village, South Jambi District, Jambi City. A descriptive qualitative approach with a case study design was employed. Six participants, comprising three fathers and three mothers of early childhood children, were purposively selected. Data were collected through in-depth interviews, observations, and documentation and analyzed using the Miles and Huberman interactive model. The credibility of the findings was ensured through source triangulation, technique triangulation, and member checking. The findings indicate that parents' understanding of digital parenting remains diverse and generally limited, with many perceiving it merely as providing access to gadgets rather than as a purposeful educational strategy. Parents also demonstrated varying approaches to selecting digital content, ranging from structured supervision using parental controls and educational applications to passive reliance on automated platform recommendations. Furthermore, consistent parental digital role modelling emerged as a crucial factor in shaping children's character. Although the findings are limited by the case study design and the small number of participants from a single community, they provide valuable contextual insights into digital parenting practices. This study highlights the importance of strengthening parents' digital literacy and promoting intentional, value-based digital parenting while offering practical implications for family education programs in similar community settings.